Fotografie moderního performativního umění: LARP - Šolcová, Tereza (Univerzita Karlova, Fakulta sociálních věd, 2021)
The objective of this bachelor thesis is to create a photo essay on the subject of modern performative art called larp. The word larp itself was formed by combining words live, action, role and playing and it is an alternative to theater and film where the actors play roles only for themselves, not for the audience. The practical part of this thesis documents the preparation, organization and the course of larp events. The theoretical part of the work briefly introduces the genre of photography of performative art, especially theater and film photography. Furthermore, this work compares these genres with the photographed theme and describes their common and different elements. This thesis also briefly deals with the history of larp as a socio-artistic phenomenon of the 21st century. Předmětem této praktické bakalářské práce je snaha o vytvoření fotografické eseje. Tématem práce je zobrazení moderního performativního umění s názvem larp, který lze volně přeložit jako hraní rolí naživo. Jedná se o alternativu například k divadlu a filmu, kde však herci hrají role pouze sami pro sebe, nikoliv pro přihlížející publikum. V praktické části práce je zdokumentována příprava, organizace i samotný průběh takových akcí. V teoretické části práce stručně představuje žánr fotografie performativního umění, a to především divadelní a filmovou fotografii. Dále pak tyto žánry srovnává s fotografovaným tématem a popisuje jejich společné a odlišné prvky. Práce se také stručně věnuje historii larpu jako sociálně-uměleckého fenoménu 21. století. Katedra žurnalistiky Department of Journalism Faculty of Social Sciences Fakulta sociálních věd